Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
[tex](2x^2+2x+1)-(7x^2+2x+15)=-5x^2-14[/tex]
Step-by-step explanation:
To explain how to approach this question, I am going to place letters in the blank spaces:
[tex](ax^2+bx+c)-(dx^2+ex+f)=-5x^2-14[/tex]
First, compare the coefficients of the x² terms on both sides of the equation: [tex]a - d = -5[/tex]
Therefore, we need to choose any two numbers in place of a and d whose difference is -5:
⇒ a = 2 and d = 7 as 2 - 7 = -5.
Similarly, upon comparing the coefficients of the x terms, we can see that there is no x term on the right side of the equation. Therefore, we need to choose numbers in place of b and e for which the difference is zero. So b and e should be the same number:
⇒ b = 2 and e = 2 as 2 - 2 = 0.
Finally, compare the constant term on both sides of the equation: [tex]c - f = -14[/tex]
Therefore, we need to choose any two numbers in place of c and f whose difference is -14:
⇒ c = 1 and f = 15 as 1 - 15 = -14.
Plug in the numbers in place of the letters on the left side of the equation:
[tex](2x^2+2x+1)-(7x^2+2x+15)=-5x^2-14[/tex]
Check
Remove the brackets:
[tex]2x^2+2x+1-7x^2-2x-15=-5x^2-14[/tex]
Collect like terms:
[tex]2x^2-7x^2+2x-2x+1-15=-5x^2-14[/tex]
Combine like terms:
[tex]-5x^2-14=-5x^2-14[/tex]
Hence proving that the left and right sides of the equation are the same.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.